An integrative review of negative emotions of older adults in later life. Issue 6 (13th August 2022) - Adolfo, Cris S.; Albougami, Abdulrhman Saad B.; Roque, Mark Y.; Aruta, John Jamir Benzon R.; Almazan, Joseph U.
Abstract: Background: Older adults are one of the most vulnerable populations requiring scientific, psychological, and clinical attention. Although several studies have explored psychoemotional needs in later life, one critical gap in the literature is a shortage of studies comprehensively reviewing negative emotional experiences and their antecedents associated with later life. Aim: This integrative review aims to identify negative emotional experiences during older adult years. Methods: This review of articles from Medline, CINAHL, Science Direct, Web of Science, ProQuest, and Taylor and Francis synthesized negative emotional experiences during older adult years. Across these six electronic databases, we searched and identified 17 relevant articles from 2005 to 2020 containing quantitative, qualitative, and mixed‐method studies. Results: Based on the review, we identified five negative emotions (sadness, anxiety, frustration, anger, and loneliness). These negative emotions were rooted in marital problems, separation from families, medical problems, physical functioning and disability, and financial limitations. Additionally, we identified common antecedents of negative emotions. Conclusion: At the center of numerous interventions, older adults are reinvigorated to understand the antecedents of negative emotions. The complex array of emotions, specifically regrets and frustration in later life, is depicted by more negativity than positivity. Such array of emotions could help develop strategies to prevent the causes of regret and frustration that nurses see when working with older adults in a clinical practice setting.